DEVELOPMENT STRATEGY FOR SATE MARANGGI GASTRONOMY TOURISM IN PURWAKARTA REGENCY - Putra Hanifan Graha; Fanji Lesmana; Silvia Septiyani Koswara; Indah Kesuma Wardani Gafar (Politeknik Pariwisata Palembang, 2025)
Gastronomy tourism is a sector with significant potential for enhancing tourist attraction and empowering the local economy. Sate Maranggi, a distinctive culinary dish from Purwakarta Regency, possesses unique cultural value and taste, making it a potential icon for gastronomy tourism. This research aims to examine the development strategy for Sate Maranggi gastronomy tourism, focusing on aspects of product quality, business actor empowerment, promotion, and multi-stakeholder collaboration. The research method uses a qualitative approach with data collection through in-depth interviews, field observations, and documentary studies. The research results indicate that the development of Sate Maranggi culinary tourism requires synergy between improving product quality, human resource training, digital marketing innovation, and support from government policies. This study concludes that an integrated strategy can enhance the competitiveness and sustainability of Sate Maranggi gastronomy tourism in Purwakarta.